GEORGIA-RUSSIA: IN SEARCH OF CIVILIZED RELATIONS - MATSABERIDZE, Malkhaz (CENTRAL ASIA AND THE CAUCASUS, 2007)
The relations between Georgia and Russia, which can hardly be called well-ordered, have escalated beyond the bilateral level to become a problem that has caught international attention. Some forces are trying to profit from the present state of affairs, while others are doing their best to bring order to bilateral relations. To achieve this, we should go to the root of the current tension. It is highly tempting to find a scapegoat, but I cannot describe myself as an impartial observer qualified to do this. It is equally wrong “to spread the guilt between the sides” and boast of an objective and unbiased approach. I have undertaken here to discuss the key issues responsible for the current situation and the far from simple quest for a model of civilized relations. The time has come to bury the past and take a look at the post-Soviet period, during which, it must be said, Georgian-Russian relations have been neither normal nor civilized. Russia is convinced that Georgia’s efforts to move closer to the West, its close contacts with the United States, and its loudly announced intention to integrate into the Euro-Atlantic structures are nothing more than manifestations of its hostile anti-Russian policy. Georgia is firmly convinced that Russia has not yet abandoned its imperial designs in the republic and is guilty of double standards: while paying lip service to Georgia’s sovereignty and territorial integrity, it is not only actively supporting the breakaway regimes in Sukhumi and Tskhinvali, but also intends to annex both regions. The publications (mainly those that appear in both countries) on Georgian-Russian relations brim with mutual accusations and reproaches. To sort things out, we should first discuss the main stereotypes and myths: to achieve civilized and rational relations we should expose and push them aside. “Ungrateful Georgians” and the “the enemy disguised as a friend.” The following opinions in Russia have survived the death of the Russian Empire and the Soviet Union to be reproduced in our time.